Lupus vulgaris mimicking cutaneous leishmaniasis: A case report - Nouf Faihan Bin Rubaian; Haya Fahad Alzamami; Gadah Abdulatif Alhosawi; Leena Abdulrahman Almuhaish (Our Dermatology Online, 2022)
Lupus vulgaris (LV) is a progressive, chronic form of cutaneous tuberculosis (CTB). The head and neck regions are the most commonly affected sites, followed by the arms and legs. Occurring in unusual sites may pose diagnostic difficulties. Herein, we report a case of LV present on the dorsal aspect of the right hand in a twenty-year-old Saudi male. It was misdiagnosed as leishmaniasis as the patient lived in an area in which it was endemic, and was treated accordingly with no benefit. A skin punch biopsy was taken and the diagnosis of LV was confirmed. The lesion responded well to anti-tubercular therapy (ATT), yet healed with atrophic scarring. Although rare, clinicians must be aware of the importance of considering CTB as an important differential, as misdiagnosis or delayed diagnosis of this entity may eventually cause prolonged morbidity.